INTEGRATED CURRICULUM LEARNING PROCESS THROUGH SCIENTIFIC APPROACH BASED ON VALUE INQUIRY OBSERVATION IN BLITAR - W Widayati (Faculty of Education Universitas Negeri Malang, 2018)
Intention of this research is to gather a right learning model that improving an integrated curriculum quality through a scientific approach for elementary school student. This research using the developing model Borg and Gall did. The result of this activities are (1) to find alternative model of integrated curriculum Learning process with scientific approach that lead student to process the subject of matter with doing, feeling, proving, and describing activity in the class and not just memorize the topic. (2) student learning activity showing the improvement of problem solving skill in the group. (3) student creativity showing an improvement of the style on their learning process. They are not only coming to school just for stead to listen the teacher instruction and do the task that given but also, they can change their style of study with observation, identification, analyzing, comparing and proving activity. (4) to held a pleasant condition in group. The result of the research showing the highest score. Almost 85%-100% of the objective that been reached. This result of research in recorded to CD that accommodating of the integrated curriculum learning strategy with scientific approach based on value inquiry. The implication of research has to follow by the teacher of elementary school with improving their performance to increasing the quality of learning process and to reach out the effective of an integrated curriculum learning process. Keywords: integrated curriculum, scientific approach